Hubungan Ketinggian Tempat dan C-organik Tanah Dengan Infeksi FAM Pada Perakaran Tanaman Kopi (Coffea Sp) di Kabupaten Dairi - M. Ihsan Al Harista Sinaga; Hardy Guchi; Alida Lubis (Universitas Sumatera Utara, 2015)
Research in Dairi aims to determine the relationship between altitude and soil organic carbon content of the ability FAM infection through stages of field sampling and direct observation in the laboratory , conducted from December 2013 - January 2014. The object is the roots of coffee plants , given the pre- observation treatment by 10% KOH soaking , HCl 2 % soaking and in a solution of trypan blue soaking . Then do the calculation ability of mycorrhizal infection by comparing the number of infected root surface and the total of roots surface were observed . The results showed that the degree of mycorrhizal infection on the roots of coffee plants positively influenced by altitude and soil organic Carbon content.Keywords: Mycorrhizae, Coffee Plant, Altitude, Organic Carbon